A surface modification method of pyrochlore oxide and its application
Through the surface modification of the oxide of the roasted greenstone, the problem of low electrochemical activity and the high amount of precious metal elements are solved, and the high -efficiency and low -cost electrocular oxygen reactions are achieved, which is suitable for electrolytic water -based hydrogen technology.
Patent Information
- Application Number
- CN202410928488.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-11
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-07-11
AI Technical Summary
The existing calcinite oxides have low electrochemical activity in electrochemical oxygen evolution reactions and high amount of precious metal elements, which limits the energy conversion efficiency and cost-effectiveness of electrolytic water hydrogen production technology.
By using anti -hemoglobin, the surface modification is performed on the surface modification of the oxides of roasted emerald, and the surface A2O3 passivation layer is etched, exposing the site of high catalytic activity, and the stretching response of the crystal surface on the surface of the crystal surface through the dual function of acidity and reduction. Harmony is distorted.
A significant improvement of the electrical oxygen response activity of roasted greenstone oxides, reducing the amount of precious metal elements, the improvement of cost benefits, and maintaining the stability and safety of the catalyst.
Smart Images

Figure CN118754219B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic materials, and in particular relates to a surface modification method of pyrochlore oxide and application thereof. Background Art
[0002] The continuous development of the global economy and industry has led to a surge in energy demand, but the excessive use of fossil fuels has caused environmental pollution and climate warming. In order to reduce carbon emissions, it is urgent to vigorously develop green, low-carbon, sustainable and clean energy. As a clean energy source, hydrogen has attracted widespread attention because its only byproduct is water vapor, and it does not produce pollutants or greenhouse gases. Compared with hydrogen production by natural gas reforming, hydrogen production by water electrolysis driven by electricity produced by renewable energy is an environmentally friendly, simple process, and high-purity hydrogen production method, which can largely solve the problems of energy shortage and environmental pollution.
[0003] The core reactions of water electrolysis for hydrogen production are oxygen evolution reaction at the anode and hydrogen evolution reaction at the cathode. Compared with the cathode hydrogen evolution reaction, the anode oxygen evolution reaction involves a complex four-electron process with more sluggish reaction kinetics, which restricts the energy conversion efficiency of water electrolysis hydrogen production technology. In order to improve the reaction rate of water electrolysis and enhance the efficiency of water electrolysis hydrogen production, the development of efficient oxygen evolution reaction catalysts is the key. At present, iridium oxide (IrO2) is the anode oxygen evolution catalyst used in commercial electrolyzer stacks, which has excellent oxygen evolution catalytic activity and stability. However, its scarcity and high cost restrict the large-scale development of water electrolysis hydrogen production technology. Therefore, exploring low-cost, high-activity and durable oxygen evolution electrocatalysts is the key to the large-scale application of water electrolysis hydrogen production technology. Compared with Ir, Ru has significantly lower cost, and its price is only one-tenth of Pt. RuO2 has very high electrochemical oxygen evolution catalytic activity, but its stability is poor, resulting in the current mainstream commercial OER catalysts mostly using IrO2. In order to accelerate the industrialization development of water electrolysis hydrogen production technology, it is particularly important to reduce the content of noble metals in the anode.
[0004] The structural formula of pyrochlore oxide is A2B2O7, which is characterized by a highly ordered cation arrangement, with the A-site and B-site cations located at different lattice positions, usually with the A-site being larger and the B-site being smaller. Pyrochlore oxides such as Bi2Ru2O7 are reported to have excellent electrochemical oxygen evolution stability, and by adjusting the composition of the A-site and B-site cations, it is beneficial to reduce the amount of precious metal elements such as Ru, etc., which has a cost advantage. However, the electrochemical activity of existing pyrochlore oxides is still relatively low, and how to improve the electrochemical activity of pyrochlore oxides is still a problem that needs to be solved. Summary of the invention
[0005] In order to overcome at least one of the problems existing in the above-mentioned prior art, one of the objects of the present invention is to provide a surface modification method of pyrochlore oxide, which can modify the surface of pyrochlore oxide to improve its electrochemical activity, and the method is simple, mild, safe and efficient.
[0006] A second object of the present invention is to provide a surface-modified pyrochlore oxide obtained by the above-mentioned surface modification method.
[0007] A third object of the present invention is to provide a catalyst comprising the above-mentioned surface-modified pyrochlore oxide.
[0008] A fourth object of the present invention is to provide an application of the above catalyst in the production of hydrogen by electrolysis of water.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is:
[0010] The first aspect of the present invention provides a method for surface modification of a pyrochlore oxide, comprising the following steps: performing surface modification treatment on the pyrochlore oxide using ascorbic acid to obtain a surface-modified pyrochlore oxide.
[0011] The inventive concept of the present invention is: the present invention has found that since pyrochlore oxide needs to be prepared under high temperature conditions to form a specific pyrochlore crystal phase structure, and during the high temperature phase formation process of pyrochlore oxide, A 3+ It is easy to segregate on the lattice surface, resulting in the appearance of an A2O3 passivation layer on the surface. This may be due to the fact that A 3+ The radius of the ion is significantly larger than that of B 4+ , resulting in lattice mismatch during high-temperature phase formation, making A 3+ Segregation occurs on the lattice surface, and this surface segregated A2O3 has basically no catalytic activity, poor conductivity, and also covers the active site B. Based on the above findings, the present invention utilizes the dual functional properties (acidity and reducibility) of ascorbic acid to perform surface modification on pyrochlore oxide, which can etch the A2O3 passivation layer to expose sites with high catalytic activity, thereby improving the electrochemical activity of pyrochlore oxide.
[0012] Preferably, the ascorbic acid is used in the form of a solution for surface modification, and the concentration of the ascorbic acid solution is 0.1 to 5 mol / L; more preferably 0.2 to 4 mol / L; and even more preferably 0.3 to 3 mol / L.
[0013] Preferably, the surface modification treatment is performed 1 to 5 times; more preferably 1 to 4 times; and even more preferably 1 to 3 times.
[0014] Preferably, the surface modification treatment time is 0.1 to 5 h; more preferably 0.3 to 4.5 h; and even more preferably 0.5 to 4 h.
[0015] Preferably, the temperature of the surface modification treatment is 80-120°C; more preferably 85-115°C; further preferably 90-110°C.
[0016] Preferably, the structural formula of the pyrochlore oxide is A2B2O7, A is at least one element selected from the group consisting of Ca, Na, U, TR, Y, Th, Pb, Sr and Bi, and B is at least one element selected from the group consisting of Ti, Zr, Nb, Ta, W, Mo and Ru.
[0017] Preferably, A is at least one element selected from the group consisting of Ca, Na, Y, Pb, Sr and Bi; further preferably, A is at least one element selected from the group consisting of Pb, Sr and Bi; and even more preferably, A is Bi.
[0018] Preferably, B is at least one element selected from Ti, Zr, W, Mo or Ru; further preferably, B is at least one element selected from W, Mo or Ru; and even more preferably, B is Ru.
[0019] In some specific embodiments of the present invention, the structural formula of the pyrochlore oxide is Bi2Ru2O7.
[0020] In some specific embodiments of the present invention, the crystal surface of the pyrochlore oxide contains an A2O3 passivation layer, and the A2O3 passivation layer is composed of A in the pyrochlore oxide. 3+ Ion segregation is formed.
[0021] In some specific embodiments of the present invention, the pyrochlore oxide is prepared by a high temperature phase formation reaction.
[0022] The present invention has found through research that pyrochlore oxides usually require a higher phase formation temperature. For example, when pyrochlore oxides are synthesized by the sol-gel method, a sintering temperature of 900°C or above is usually required. A 3+ The surface segregation of cations forms an A2O3 passivation layer on the crystal surface, thereby reducing the catalytic activity and conductivity. The present invention improves the electrocatalytic activity of the pyrochlore oxide obtained by high-temperature phase reaction by surface modification.
[0023] Preferably, the temperature of the high-temperature phase-forming reaction is 500-1500°C; more preferably, 700-1400°C; and even more preferably, 800-1200°C.
[0024] In some specific embodiments of the present invention, the raw materials for preparing the pyrochlore oxide include a compound containing element A and a compound containing element B.
[0025] In some more specific embodiments of the present invention, the compound containing element A includes a salt, an oxide or a combination thereof containing element A.
[0026] In some more specific embodiments of the present invention, the compound containing the B element includes a salt, an oxide or a combination thereof containing the B element.
[0027] In some more specific embodiments of the present invention, the molar ratio of the compound containing element A to the compound containing element B is (1-1.5):1.
[0028] In some specific embodiments of the present invention, the raw materials for preparing the pyrochlore oxide further include a complexing agent, and the complexing agent includes but is not limited to citric acid.
[0029] In some more specific embodiments of the present invention, the high temperature phase formation reaction includes at least one of a solid phase synthesis method, a sol-gel method or a hydrothermal synthesis method; in some specific embodiments of the present invention, the high temperature phase formation reaction is selected from a sol-gel method.
[0030] The second aspect of the present invention provides a surface-modified pyrochlore oxide according to the first aspect of the present invention, which is prepared by the surface modification method according to the first aspect of the present invention.
[0031] The third aspect of the present invention provides a catalyst comprising the surface-modified pyrochlore oxide according to the first aspect of the present invention.
[0032] The fourth aspect of the present invention provides an application of the catalyst described in the third aspect of the present invention in producing hydrogen by electrolysis of water.
[0033] The beneficial effects of the present invention are as follows: the present invention utilizes the dual functional properties of ascorbic acid, namely, acidity and reducing property, to modify the surface of pyrochlore oxide, etches the passivation layer contained on the surface, exposes sites with high catalytic activity, and after the surface treatment, tensile strain is generated on the crystal surface, resulting in a large amount of lattice distortion. This change in the distance between lattice atoms causes the energy level of its outer electrons to change, significantly improving the electrochemical reaction activity of the pyrochlore oxide material. The surface-modified pyrochlore oxide obtained by the present invention is widely used as a catalyst, especially as a catalyst for hydrogen production by electrolysis of water.
[0034] Specifically, compared with the prior art, the present invention has the following advantages:
[0035] 1. The pyrochlore oxide used in the present invention not only has excellent electrochemical oxygen evolution stability, but also has cost advantages and can reduce the amount of precious metal elements used. Taking Bi2Ru2O7 as an example, the mass fraction of Ru contained in it is about 27.6wt.%, which is much lower than the mass fraction of RuO2 contained in it (76wt.%). Therefore, the surface-modified pyrochlore oxide obtained by the method of the present invention has both good catalytic activity and low cost advantages.
[0036] 2. The surface modification degree of pyrochlore oxide can be controlled by adjusting the concentration of ascorbic acid solution, the number of treatments and the time. The surface-modified pyrochlore oxide is applied to the oxygen evolution reaction and exhibits excellent electrocatalytic activity and stability.
[0037] 3. The surface modification method of the present invention can be carried out at room temperature, with simple raw materials, concise process flow, easy operation, suitable for large-scale preparation, green and safe reaction process, and no dangerous chemical reagents such as sodium borohydride and hydrazine hydrate are used. It has the advantages of being simple, mild, safe and efficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The XRD diagrams of the catalyst samples of Examples 1 to 3 of the present invention and Comparative Example 2 are shown.
[0039] Figure 2 HRTEM images of the catalyst samples of Example 2 of the present invention and Comparative Example 2.
[0040] Figure 3 It is a comparison chart of the LSV performance of the catalyst samples of Examples 1 to 3 of the present invention and Comparative Examples 1 to 2.
[0041] Figure 4 This is a comparison chart of the LSV performance of the catalyst samples of Examples 2, 4, 5 of the present invention and Comparative Example 2.
[0042] Figure 5 The catalyst samples of Example 2 and Comparative Example 2 of the present invention were tested at 10 mA·cm -2 Comparison of LSV performance before and after 2000 CV cycles at different current densities. DETAILED DESCRIPTION
[0043] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples and comparative examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.
[0044] In some embodiments of the present invention, a method for surface modification of a pyrochlore oxide is provided, comprising the following steps: performing surface modification treatment on the pyrochlore oxide using ascorbic acid to obtain a surface-modified pyrochlore oxide.
[0045] In some embodiments of the present invention, ascorbic acid is surface-modified in the form of a solution, and the concentration of the ascorbic acid solution is 0.1 to 5 mol / L; in some specific embodiments of the present invention, the concentration of the ascorbic acid solution is 0.2 to 4 mol / L; in some examples of the present invention, the concentration of the ascorbic acid solution is 0.3 to 3 mol / L; non-limiting specific examples are 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L or 2.5 mol / L.
[0046] In some embodiments of the present invention, the number of surface modification treatments is 1 to 5 times; in some specific embodiments of the present invention, the number of surface modification treatments is 1 to 4 times; in some examples of the present invention, the number of surface modification treatments is 1 to 3 times; non-limiting specific examples are 1 time, 2 times or 3 times.
[0047] In some embodiments of the present invention, the surface modification treatment time is 0.1 to 5 hours; in some specific embodiments of the present invention, the surface modification treatment time is 0.3 to 4.5 hours; in some examples of the present invention, the surface modification treatment time is 0.5 to 4 hours; non-limiting specific examples are 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours or 3.5 hours.
[0048] In some embodiments of the present invention, the temperature of the surface modification treatment is 80-120°C; in some specific embodiments of the present invention, the temperature of the surface modification treatment is 85-115°C; in some examples of the present invention, the temperature of the surface modification treatment is 90-110°C; non-limiting specific examples are 95°C, 100°C or 105°C.
[0049] In some embodiments of the present invention, the structural formula of the pyrochlore oxide is A2B2O7, A is at least one element selected from Ca, Na, U, TR, Y, Th, Pb, Sr or Bi, and B is at least one element selected from Ti, Zr, Nb, Ta, W, Mo or Ru.
[0050] In some specific embodiments of the present invention, A is at least one element selected from Ca, Na, Y, Pb, Sr or Bi; in some examples of the present invention, A is at least one element selected from Pb, Sr or Bi; in some specific examples of the present invention, A is Bi.
[0051] In some specific embodiments of the present invention, B is at least one element of Ti, Zr, W, Mo or Ru; in some examples of the present invention, B is at least one element of W, Mo or Ru; in some specific examples of the present invention, B is Ru.
[0052] In some specific embodiments of the present invention, the structural formula of the pyrochlore oxide is Bi2Ru2O7.
[0053] In some embodiments of the present invention, the crystal surface of the pyrochlore oxide contains an A2O3 passivation layer, and the A2O3 passivation layer is composed of A in the pyrochlore oxide. 3+ Ion segregation is formed.
[0054] In some embodiments of the present invention, the pyrochlore oxide is prepared by a high temperature phase formation reaction.
[0055] In some embodiments of the present invention, the temperature of the high-temperature phase reaction is 500-1500°C; in some specific examples of the present invention, the temperature of the high-temperature phase reaction is 700-1400°C; in some specific examples of the present invention, the temperature of the high-temperature phase reaction is 800-1200°C; non-limiting specific examples are 900°C, 1000°C or 1100°C.
[0056] In some embodiments of the present invention, the raw materials for preparing the pyrochlore oxide include a compound containing element A and a compound containing element B.
[0057] In some embodiments of the present invention, the compound containing element A includes a salt, an oxide or a combination thereof containing element A.
[0058] In some embodiments of the present invention, the compound containing the B element includes a salt, an oxide or a combination thereof containing the B element.
[0059] In some embodiments of the present invention, the molar ratio of the compound containing element A to the compound containing element B is (1-1.5):1.
[0060] In some embodiments of the present invention, the raw materials for preparing pyrochlore oxide further include a complexing agent, and the complexing agent includes but is not limited to citric acid.
[0061] In some embodiments of the present invention, the high temperature phase forming reaction comprises at least one of a solid phase synthesis method, a sol-gel method or a hydrothermal synthesis method; in some specific embodiments of the present invention, the high temperature phase forming reaction is selected from a sol-gel method.
[0062] In some examples of the present invention, the pyrochlore oxide is prepared by a method comprising the following steps: mixing various preparation raw materials to perform a gelation reaction, and performing a high-temperature phase formation reaction in an oxygen-containing atmosphere to obtain the pyrochlore oxide.
[0063] The following is a further description with reference to more specific embodiments and comparative examples.
[0064] In the following examples and comparative examples, room temperature refers to 20 to 30°C.
[0065] Example 1
[0066] A surface modification method of pyrochlore oxide Bi2Ru2O7 (BRO), comprising the following steps:
[0067] 1) Preparation of pyrochlore oxide Bi2Ru2O7: Bi2Ru2O7 in this example is prepared by sol-gel method, and the specific steps are as follows: bismuth nitrate (Bi(NO3)3·5H2O, 0.6mmol), ruthenium trichloride (RuCl3, 0.5mmol) and citric acid (2.2mmol) are dissolved in 30mL of deionized water, and 1mL of nitric acid solution is added dropwise and mixed evenly. The mixed solution is placed in a water bath, the water bath temperature is set to 90℃ and the solution is continuously stirred magnetically, and the prepared gel is placed in a drying oven, and the temperature is set to 170℃ for 6 hours. Subsequently, the dried powder is transferred to a corundum crucible and placed in a muffle furnace for heating, and the temperature is increased from room temperature to 600℃ at a heating rate of 5℃ / min, and the temperature is maintained for 2 hours; then the temperature is increased to 900℃ at a heating rate of 5℃ / min, and the temperature is maintained for 8 hours. After the procedure is completed and the muffle furnace is cooled to room temperature, pyrochlore oxide Bi2Ru2O7 is obtained.
[0068] 2) Surface modification: The Bi2Ru2O7 obtained in step 1) was placed in 20 mL of ascorbic acid solution (0.5 mol / L), heated in a water bath at 95°C with stirring for 1 h, then centrifuged and washed three times with deionized water, then centrifuged and washed once with ethanol, placed in an oven and dried at 80°C for 8 h, and finally taken out and ground for 10 min to obtain a surface-modified pyrochlore oxide sample, which was recorded as BRO AA1.
[0069] Example 2
[0070] A method for surface modification of pyrochlore oxide Bi2Ru2O7 (BRO), which differs from Example 1 in that, in step 2) of this example, the surface modification treatment is carried out twice using ascorbic acid solution, specifically, the steps of placing in ascorbic acid solution for water bath heating and stirring, deionized water centrifugal washing, and ethanol centrifugal washing are repeated twice, and other raw materials and preparation conditions are the same as in Example 1. The obtained sample is recorded as BRO AA2.
[0071] Example 3
[0072] A surface modification method for pyrochlore oxide Bi2Ru2O7 (BRO) is disclosed, which differs from Example 1 in that, in step 2) of this example, the surface modification treatment is carried out three times using an ascorbic acid solution, specifically, the steps of placing in an ascorbic acid solution for water bath heating and stirring, centrifugal washing with deionized water, and centrifugal washing with ethanol are repeated three times, and other raw materials and preparation conditions are the same as in Example 1. The obtained sample is recorded as BRO AA3.
[0073] Example 4
[0074] A surface modification method of pyrochlore oxide Bi2Ru2O7 (BRO) is disclosed, which differs from Example 1 in that in step 2) of this example, the concentration of the ascorbic acid solution is 2 mol / L, and the other raw materials and preparation conditions are the same as those in Example 1. The obtained sample is recorded as BRO AA4.
[0075] Example 5
[0076] A surface modification method for pyrochlore oxide Bi2Ru2O7 (BRO), which differs from Example 1 in that in step 2) of this example, the time for heating and stirring in a water bath in an ascorbic acid solution is 3 hours, that is, the ascorbic acid treatment time is 3 hours, and other raw materials and preparation conditions are the same as in Example 1. The obtained sample is recorded as BRO AA5.
[0077] Comparative Example 1
[0078] In this example, commercial RuO2 (produced by Shanghai MacLean Reagent Company) was used as the catalyst sample.
[0079] Comparative Example 2
[0080] A pyrochlore oxide Bi2Ru2O7 (BRO) catalyst is different from Example 1 in that the surface modification treatment with ascorbic acid solution in step 2) is not performed in this example, and other raw materials and preparation conditions are the same as those in Example 1. The obtained sample is recorded as BRO-initial.
[0081] Performance Testing
[0082] 1) Morphological structure characterization: XRD patterns and high-resolution transmission electron microscopy (HRTEM) images of the samples obtained in Examples 1 to 5 of the present invention and Comparative Examples 1 to 2 were tested.
[0083] 2) Electrochemical hydrogen evolution performance test: The samples obtained in Examples 1 to 5 of the present invention and Comparative Examples 1 to 2 were used as catalyst samples to conduct an oxygen evolution performance test, which specifically includes the following steps:
[0084] (1) Preparation of working electrode: 5 mg of samples of Examples 1 to 5 and Comparative Examples 1 to 2 and 1 mg of carbon black were dispersed in a mixed solution of 0.8 mL of water, 0.17 mL of isopropanol and 0.03 mL of 5 wt.% Nafion. After ultrasonic homogenization, 10 uL of the suspension was transferred and dropped on the polished glassy carbon electrode surface. After natural drying, the electrocatalytic test was performed.
[0085] (2) Oxygen evolution performance test: The oxygen evolution performance test was conducted on an electrochemical workstation using a glassy carbon electrode loaded with a catalyst sample as the working electrode, saturated calomel (SCE) as the reference electrode, a platinum mesh as the counter electrode, and a 1M KOH aqueous solution as the electrolyte. The hydrogen evolution catalytic performance was evaluated by polarization curve testing. By applying 10 mA cm -2 The working current density is used to measure the change of electrode voltage over time (more than 10 hours), that is, the electrochemical hydrogen evolution stability of the catalyst is evaluated through the chronopotentiometry curve.
[0086] Figure 1 The XRD patterns of the catalyst samples of Examples 1 to 3 and Comparative Example 2 of the present invention, wherein a is the XRD pattern with a 2θ angle of 10 to 80°, PDF#81-23228 refers to the Bi2Ru2O7 standard, and b is the XRD partial enlarged pattern with a 2θ angle of 29 to 31°. Figure 1 It can be seen that the samples after surface modification in Examples 1 to 3 have basically the same crystal structure as the sample in Comparative Example 1 that has not been surface modified, but the diffraction angle shifts to a lower angle, indicating that the BRO material lattice expands as the number of ascorbic acid treatments increases.
[0087] Figure 2 The HRTEM images of the catalyst samples of Example 2 and Comparative Example 2 of the present invention are shown in Figure 1, where a is the HRTEM image of the sample of Comparative Example 2 and b is the HRTEM image of the sample of Example 2. Figure 2From a and b, it can be seen that the surface of the sample in comparative example 2 (BRO-initial) is smooth and regular, while the surface of the sample in example 2 (BRO-AA2) is rough, which indicates that ascorbic acid can etch the surface of BRO and remove the bismuth oxide passivation layer segregated on the surface of BRO, thereby exposing a large number of catalytic active sites. In addition, by accurately measuring the lattice fringe spacing of the rough surface particles in example 2, the crystal plane spacing result obtained is 0.203nm, corresponding to the (422) crystal plane, which is wider than the (422) crystal plane diffraction fringe spacing of comparative example 2 (0.197nm), indicating that ascorbic acid reduces the surface of BRO and expands its lattice, and this result can correctly correspond to the XRD result. This change in the distance between lattice atoms may change the energy level of its outer electrons, which is beneficial to improve the electrochemical reaction activity of pyrochlore oxide materials.
[0088] Figure 3 The linear sweep voltammetry (LSV) performance comparison diagram of the catalyst samples of Examples 1 to 3 of the present invention and Comparative Examples 1 to 2 is shown in the figure. It can be clearly seen that compared with Comparative Examples 1 to 2, Examples 1 to 3 all show significantly better catalytic activity in oxygen evolution reaction, indicating that the treatment of pyrochlore oxide BRO with ascorbic acid can indeed significantly improve its catalytic activity.
[0089] Figure 4 The linear sweep voltammetry (LSV) performance comparison diagram of the catalyst samples of Examples 2, 4, and 5 of the present invention and Comparative Example 2. -2 The corresponding oxygen evolution overpotentials are 352, 431 and 423 mV, respectively. Compared with Examples 4 to 5, Example 2 exhibits better catalytic performance for oxygen evolution reaction.
[0090] Test Examples 1 to 5 and Comparative Examples 1 to 2 at 10 mA·cm -2 The oxygen evolution overpotential under the current density is recorded in Table 1.
[0091] Table 1 Examples 1 to 5 and Comparative Examples 1 to 2 samples at 10 mA·cm -2 Overpotential at current density
[0092] Overpotential / mV Example 1 305 Example 2 264 Example 3 338 Example 4 352 Example 5 345 Comparative Example 1 410 Comparative Example 2 357
[0093] Figure 5The samples of Example 2 and Comparative Example 2 of the present invention were subjected to electrochemical cyclic voltammetry (CV) stability tests in 1M KOH electrolyte, with a voltage scan interval of 1.4 to 1.65 V, a voltage scan rate of 100 mV / s, and a scan number of 2000 cycles. It can be seen from the figure that the polarization curves of the samples of Example 2 and Comparative Example 2 have almost no change before and after the CV cycle, indicating that they both exhibit excellent electrochemical stability during the oxygen evolution reaction stability test. Specifically, after 2000 CV cycles, the samples of Example 2 and Comparative Example 2 have a 10 mA·cm -2 The potential changes corresponding to the current density were 2 and 4 mV respectively, and the performance changes were very small before and after the stability test.
[0094] During the high temperature phase formation process of Bi2Ru2O7, Bi 3+ It is easy to segregate on the lattice surface, resulting in a Bi2O3 passivation layer on the surface. This may be due to Bi 3+ The radius of the ion is significantly larger than that of Ru 4+ , resulting in lattice mismatch during high temperature sintering, making Bi 3+ Segregation occurs on the lattice surface. This surface segregated Bi2O3 has basically no catalytic activity, poor conductivity, and will also cover the active site Ru. Therefore, in Examples 1 to 5 of the present invention, Bi2Ru2O7 is mixed with an ascorbic acid solution, and the bifunctional properties (acidity and reducibility) of ascorbic acid are used to treat the surface of the Bi2Ru2O7 oxide, and the Bi2O3 enriched in the A position on the surface of the bismuth ruthenate is etched to expose sites with high catalytic activity. There is tensile strain and a large amount of lattice distortion on the surface of the bismuth ruthenate after ascorbic acid. This change in the distance between lattice atoms changes the energy level of its outer electrons, significantly improving the electrochemical oxygen evolution reaction activity of the Bi2Ru2O7 material.
[0095] The pyrochlore oxide sample Bi2Ru2O7 used in Examples 1 to 5 of the present invention contains a mass fraction of Ru of about 27.6wt.%, which is much lower than the mass fraction of RuO2 (76wt.%), so it not only has excellent electrochemical oxygen evolution stability, but also has cost advantages, and can reduce the amount of precious metal elements. In addition, by adjusting the concentration of the ascorbic acid solution, the number of treatments and the time, the surface modification degree of Bi2Ru2O7 can be adjusted, and the surface-modified Bi2Ru2O7 is applied to the oxygen evolution reaction, showing excellent electrocatalytic activity and stability. The surface modification method provided in the embodiment of the present invention can be carried out at room temperature, the raw materials are simple, the process flow is concise and easy to operate, it is suitable for large-scale preparation, the reaction process is green and safe, and no dangerous chemical reagents such as sodium borohydride and hydrazine hydrate are used, which has the advantages of being simple, mild, safe and efficient.
[0096] In summary, the present invention utilizes the dual functional properties of ascorbic acid, i.e., acidity and reducing properties, to modify the surface of pyrochlore oxide, and etches the passivation layer contained on its surface to expose sites with high catalytic activity. After the surface treatment, tensile strain is generated on the crystal surface, resulting in a large amount of lattice distortion. This change in the distance between lattice atoms causes the energy level of its outer electrons to change, which significantly improves the electrochemical reaction activity of the pyrochlore oxide material. The surface-modified pyrochlore oxide obtained by the present invention is widely used as a catalyst, especially as a catalyst for hydrogen production by electrolysis of water.
Claims
1. A method for surface modification of pyrochlore oxide, characterized in that: The following steps are involved: Using ascorbic acid to perform surface modification treatment on pyrochlore oxide to obtain surface modified pyrochlore oxide; The ascorbic acid is subjected to surface modification treatment in the form of a solution, and the concentration of the ascorbic acid solution is 0.1-0.5 mol / L; The number of surface modification treatments is 1 to 2 times; The surface modification treatment time is 0.1~1h; The temperature of the surface modification treatment is 80-120°C; The structural formula of the pyrochlore oxide is A2B2O7, where A is Bi and B is Ru.
2. The surface modification method according to claim 1, characterized in that: The pyrochlore oxide is prepared by a high-temperature phase-forming reaction, and the temperature of the high-temperature phase-forming reaction is 500-1500°C.
3. A surface-modified pyrochlore oxide, characterized in that: The invention is prepared by the surface modification method according to any one of claims 1 to 2.
4. A catalyst, characterized in that The surface-modified pyrochlore oxide according to claim 3 is included.
5. Use of the catalyst as claimed in claim 4 in producing hydrogen by electrolysis of water.
Citation Information
Patent Citations
Preparation of pyrochlore materials and use of pyrochlore materials in electrocatalytic oxygen production
CN109453771A
Oxygen catalyst and electrode using said oxygen catalyst
CN113412155A